Systematic compost production using cow dung and kitchen waste for sustainable waste management and manure production - Ahmed, Sharif; Miajy, Abdullah; Debnath, Manik; Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2024)
Organic matter plays a vital role in soil health, fertility, and overall agricultural productivity. In Bangladesh, the status of organic matter is influenced by various factors, including inherent soil fertility level, agricultural practices, land management, and socio-economic conditions. The soil organic matter content in Bangladesh varies significantly across regions, largely influenced by climate, soil type, and land use practices. Generally, many areas experience low levels of organic matter, typically below the desirable range of 3-5%. The average soil organic matter in Bangladeshi soil is less than 1%. This deficiency greatly impacts the productivity, profitability, and sustainability of crop production. There are several reasons behind the low organic matter content of Bangladesh soils. The main reason is the lack of organic recycling through the addition of crop residues, animal waste, kitchen waste, and other organic manures.